Health Care Resource Use and Costs for Crohn’s Disease before and after Infliximab Therapy - Dustin E Loomes; Christopher Teshima; Philip Jacobs; Richard Fedorak (Canadian Journal of Gastroenterology)
BACKGROUND: Infliximab therapy in patients with Crohn’s disease decreases resource use; however, the overall impact on health-related expenditures is unclear, especially beyond one year of study.